Acceptance strategy of HIV pre-exposure prophylaxis for female sex workers in Badung, Bali, Indonesia - Putri Pratiwi, Ni Putu; Ani, Luh Sri; Sutarsa, I Nyoman (Universitas Udayana, 2024)
Background and purpose: HIV pre-exposure prophylaxis (PrEP) is aimed to prevent the transmission of HIV infection. The use of PrEP by female sex workers (FSWs) in Badung District, Bali Province was relatively low. This study explores critical strategies to increase the acceptance of HIV PrEP program by FSWs in Badung District, Bali, Indonesia. Methods: A qualitative descriptive study was conducted in Badung District. This study involved 16 purposively selected informants consisting of 5 FSWs who had used PrEP, 5 FSWs who had not and 6 stakeholders whom involved in the PrEP implementation. Data was collected using in-depth interviews which include: strategies for strengthening self-confidence, social support, effectiveness of PrEP implementation, and accessibility of health services. Data was analyzed using a thematic approach. Results: The research highlights several key strategies to enhance the acceptance of PrEP including strengthening self-efficacy, empowering individuals with the confidence and skills to utilize PrEP effectively, bolstering of social support networks by reducing stigma and fostering a supportive environment. The effectiveness of PrEP program implementation is crucial by ensuring well-structured, responsive, and capability to meet the population needs. Finally, improving service accessibility is crucial, as it removes barriers to obtaining PrEP. Together, these strategies form a comprehensive framework for improving PrEP acceptance. Conclusion: To increase PrEP acceptance among FSWs, the primary strategy that needs to be implemented is strengthening the service sector. For this reason, it is suggested that the health office carry out outreach and increase access to health services and assistance.